(3GdQbGHI GdOGNdjI hGdJObjb aj HjFI JcfhdhLjG GdeYdheGJ (B/s - (3GdMSHGf, YWG Gddg CMeO Shjdes ((3YeGf(B: s (3OGQ GdQGjI(B, s, 2009)
(3fXGe GdQbGHI GdOGNdjI,hGbY JcfhdhLjG GdeYdheGJ aj fXGe GdQbGHI GdOGNdjIs
(3HHdjhZQGajG(B:(3U U(B.193-204s
Keywords: (3GdMGSHGJ GdEdcJQhfjIs; (3GdQbGHI GdEOGQjIs